Arar, Mahdi. “The Semantic Depth of Qur’anic Text: A Facet of the Iʿjāz (Inimitability) of the Qur’an,” Year 7, Issue 27 (Winter 1422 AH/ 2001 CE), Pp. 43-62. - عرار مهدي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2001)
Mahdi Arar’s article explains the term “infitāḥ al-dalālah” (semantic depth) on the phonetic level, citing examples from Qur’an, and using texts from al-Qasṭalānī, Ibn al-Anbārī, and others. It then discusses the morphological level related to the construction of the word, citing Qur'anic verses, the views of linguists such as al-Ṣāḥibī, al-Istrābādī, al-Mubrad, and the views of Qur'anic exegetes such as al-Qurṭubī, al-Ṭabrisī, al-Zamakhsharī, and others. It then discusses the structural level, and then the lexical level, noting that the infitāḥ al-dalālah can sometimes be countered by semantic introversion. It concludes by holding that semantic depth may lead to the increase of fiqhī (juristic) rulings contained in a single Qur'anic verse.